PENINGKATAN PENCAPAIAN KOMPETENSI SISWA KELAS VIII G SMP NEGERI 2 PARON PADA MATERI SISTEM PENCERNAAN MANUSIA DENGAN PENDEKATAN SAINTIFIK MELALUI MEDIA PUZZLE - Lukitaningsih, Tri (Jurnal Florea, 2015)
The purpose of this action research is to improve the competence learning material digestive system in class VIII G of SMP Negeri 2 Paron with scientific learning through the medium of the puzzle. Research carried out for 3 months starting in September 2014 to November 2014. The subject of this class action research was a number of 29 students. Data collection was performed by the method of observation and testing methods. Observation is aimed at three competencies: (1) the competence of attitude, (2) the competence of knowledge, (3) skills competency. The results showed that students learning competence has increased, ie if the initial reflection completeness reached 59% in the first cycle increased to 69% and in the second cycle increased to 86%. Figures incompleteess decreased if the initial reflection of 41% then the first cycle decreased to 31% and the second cycle decreased to 14%. On average class increased if the initial reflection at 69 then the first cycle increased to 71 and the second cycle increased to 75. Thus, with these results it can be said that the puzzle able to enhanced student competence Keywords: Puzzle, scientific, learning competence